DIGITAL BADGES AS REWARDS IN SCIENCE EDUCATION: STUDENTS’ PERCEPTIONS AND EXPERIENCES - Aaron A. Funa (Tạp chí Khoa học Đại học Đà Lạt)
Several studies have reported positive effects of digital badges on students’ academic performance and behavior. A digital badge serves as an indicator of an accomplishment or skill that can be showcased, accessed, and verified online. The researcher investigated how students perceive digital badges as rewards in a biology course through a phenomenological study. Gamified lesson plans and students’ portfolios were used to implement gamification and award digital badges. The study involved Filipino Grade 12 STEM students (n = 41) from a single intact class, and interviews were conducted with a subset of 10 students. By analyzing student responses in their portfolios and interviews, four key themes of digital badges were identified: class participation, learning outcomes, time management, and social interaction. The results revealed that these themes were influenced by factors such as competition, a sense of accomplishment, self-improvement, status recognition, and evidence of achievement. It was found that, while digital badges can be beneficial for high-performing students, they may have detrimental effects on low-performing students. The researcher recommended that the identified themes and their underlying drivers be considered when developing digital badges and in future studies on digital badges and gamification.